En Beretning om Afdeling AS under Statsadvokaten for særlige Anliggender for tiden april-august 1940 - Lauridsen, John T. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2016)
John T. Lauridsen: Account of Department AS under the Public Prosecutor for Special Affairs for the period April–August 1940 In the summer of 1940, the Politiken journalist Vilhelm Bergstrøm managed to get a contact in Department AS, which operated under the Public Prosecutor for Special Affairs, to write an account of the department’s activities during the period April–August 1940. The account is anonymous, but almost certainly written by Detective Inspector Roland Olsen, and is particularly interesting because Department AS dealt with all of the police cases related to Danish-German affairs. The account shows that by far the majority of the many cases (1,650) were trivial, built on rumours and faulty assumptions. The few serious cases mainly concerned the tracking-down and arrest of German emigrants. There was only a single serious case of sabotage, serious because a prank by the Germans required an example be set.